2019
DOI: 10.1111/iju.14068
|View full text |Cite
|
Sign up to set email alerts
|

Clinical staging of upper urinary tract urothelial carcinoma for T staging: Review and pictorial essay

Abstract: Upper urinary tract urothelial carcinoma is staged using the TNM classification of malignant tumors. Preoperative TNM is important for treatment planning. Computed tomography urography is now widely used for clinical survey of upper urinary tract carcinoma because of its diagnostic accuracy. Computed tomography urography is recommended as the first‐line imaging procedure in several guidelines. Several reports stated that computed tomography urography is also useful for staging. However, no educational and prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 47 publications
(86 reference statements)
0
34
0
Order By: Relevance
“…In contrast, no effective T‐staging criteria for the differentiation of OC disease in UTUC patients have been reported. The current EAU guidelines note that it is difficult to distinguish ≤pT2 disease by the available preoperative imaging modalities 5,13,14 . The present findings showed that upstaging to ≥pT2 from ≤cT1 occurred frequently; the proportion of upstaging in the UCP and UCU patients was 30.7% and 34.2%, respectively (Fig.…”
Section: Discussionmentioning
confidence: 50%
“…In contrast, no effective T‐staging criteria for the differentiation of OC disease in UTUC patients have been reported. The current EAU guidelines note that it is difficult to distinguish ≤pT2 disease by the available preoperative imaging modalities 5,13,14 . The present findings showed that upstaging to ≥pT2 from ≤cT1 occurred frequently; the proportion of upstaging in the UCP and UCU patients was 30.7% and 34.2%, respectively (Fig.…”
Section: Discussionmentioning
confidence: 50%
“…For more accurate assessment, a tumor mass should be evaluated directly by imaging examinations. CT and magnetic resonance imaging are the most common and useful examinations for a diagnosis of UTUC 10 , 11 . A tumor mass can be detected as a mass lesion with or without an irregular external surface on these images.…”
Section: Discussionmentioning
confidence: 99%
“…CTU shows high sensitivity and specificity of ≥92% in UTUC [5] . Unfortunately, CTU can only differentiate between T2 and T3 tumors with sensitivity and specificity of approximately 85%, with no certain differentiation between non–muscle-invasive (Tis/Cis, Ta, T1) and muscle-invasive (T2) tumors, which is essential for planning of conservative therapy [6] . In particular, flat lesions can escape detection, even by experienced investigators [6] .…”
mentioning
confidence: 99%
“…Unfortunately, CTU can only differentiate between T2 and T3 tumors with sensitivity and specificity of approximately 85%, with no certain differentiation between non–muscle-invasive (Tis/Cis, Ta, T1) and muscle-invasive (T2) tumors, which is essential for planning of conservative therapy [6] . In particular, flat lesions can escape detection, even by experienced investigators [6] . Magnetic resonance imaging with the current protocols (sensitivity 75%) and positron emission tomography-CT (sensitivity and specificity between 80% and 85% [7] ) suffer from lower detection rates and are not recommended routinely [1] .…”
mentioning
confidence: 99%